Design and optimization of a high efficiency CdTe–FeSi2 based double-junction two-terminal tandem solar cell - Mehedi Hasan Tonmoy; Sheikh Noman Shiddique; Ahnaf Tahmid Abir; Jaker Hossain (Heliyon, 2024)
This article theoretically demonstrates an enormously efficient CdTe–FeSi2 based dual-junction tandem solar cell accompanied by slender semiconductor layers. The peak efficiency of the device has been ensured through the optimization of its various attributes of window, CdTe (bandgap 1.5 eV) top absorber, FeSi2 (bandgap 0.87 eV) bottom absorber and back surface layers. Additionally, the impacts of thickness, doping and the level of defects in different window, base and rear surface layers have been examined to observe how different layers affect the solar cell's performance. The optimized n-CdS/p-CdTe/p+-MoS2--n-CdS/p-FeSi2/p+-Cu2SnS3 dual-junction tandem solar device displays an efficiency of 43.9% with a voltage at no load, VOC of 1.928 V, current density under a closed circuit, JSC of 25.34 mA/cm2, and fill factor of 89.88%, respectively. These results disclose the high potential of the suggested solar cell based on CdTe and FeSi2 compounds.